Pengembangan Pembelajaran al-Qur'an Hadits Surah az-Zalzalah pada Media E-Learning Berbasis Edmodo - Nurdiana , Ika Wahyu; Hamid , Abdulloh; Wahyudi , Winarto Eka (LPPPM STAI Darul Hikmah Bangkalan, 2021)
Based on the criteria of learning al-Qur'an Hadith with the material of surah az-Zalzalah, it can be said that it is valid and effective for grade IV students of Madrasah Ibtidaiyah. To compile and produce learning, it is necessary to research the development of e-learning media through edmodo. Can increase the creativity of students in learning al-Qur'an Hadith about surah az-Zalzalah using e-learning media through edmodo. This type of research is the ADDIE model that has been used in the development of Al-Qur'an Hadith learning through edmodo e-learning media. There are 5 stages in the ADDIE model, namely analysis, design, development, application and evaluation. Has been validated by 3 lecturers as validator experts, media and instruments on e-learning media through edmodo. The subjects in development research were 30 grade students for the 2020-2021 school year. Learning al-Qur'an Hadith surah az-Zalzalah can be said to be good and meet the requirements with a rating of 78.34% through the edmodo e-learning media. However, students can respond to the learning media with a rating of 82.36% and have been declared good. Thus, all aspects of e-learning media through edmodo in learning al-Qur'an Hadith surah az-Zalzalah can be categorized as good and feasible to be used in the learning process.